(3eLehYI aj GdcjejGAs
(3ChdgG (B:s
(3GdHGH GdChd ai eYQaI GdMLQ GdecQQ GdegGf GdMbjQ GdeYXe GdeTghQ HGdCaYGd GdRGFOI GdYXjeI s
(3BNQgG (B:s
(3hjTeY eQGQkG MJi jJQbe Ke jMd hjYbQ Ef TGA Gddg jUjQ GcSjQkG fajSkG JeJ TQM GdbUjOI GdYbGHjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3Jdi GdeNWhW HYV GdahGFO ddMcje Ph Gdfhf hGHf OGhO hdLGHQ Hf MjGfs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs